Hormonal profile and characteristics of polychistic ovarium syndrome among Madurese tribe, Indonesia - Zakkiyatus Zainiyah; Eny Susanti; Mustofa Haris (International Journal of Public Health Science (IJPHS), 2020)
Polycystic ovarium syndrome (PCOS), the most common endocrine disorders in women of reproductive age, characterized by menstrual disorders (amenorrhea/oligomenorrhea), hirsutism, the appearance of acne, alopecia and the results of biochemical tests that show increased androgens (testosterone). Increased serum luteinizing hormone (LH) and follicle stimulating hormone (FSH) serve as diagnostic tests for PCOS over the years, but from several research results obtained inconsistent results that need further research. The purpose of this study is to analyze the hormonal profile and characteristics of polycystic ovary syndrome (PCOS) in Madura. Case-control study conducted in March-August 2019 in the Madura tribe. There were 32 subjects with PCOS and 32 healthy women participated in this study. Hormonal examination was using a serum and followed by enzyme-linked immune sorbent assay (ELISA kit). Levels Follicle-stimulating hormone (FSH) average was 8.74 and SHBGs were 10.02 lower in PCOS patients and LH levels were higher in PCOS patients; ratio LH/FSH was 0.76. The results of the Madurese study showed that levels of FSH, LH, weight significantly related to PCOS sex hormone binding globulin (SHBG), however body mass index (BMI) levels were not related to PCOS.